2021
DOI: 10.1177/87564793211002502
|View full text |Cite
|
Sign up to set email alerts
|

Competency-Based Methods in Adult Cardiac Sonography and its Application to Credentialing

Abstract: Objectives: This research examined the effects of multiple combined competency-based methods in an adult cardiac Commission on Accreditation of Allied Health Education Programs (CAAHEP) accredited diagnostic medical sonography program on clinical and didactic scores. Materials and Methods: A quasi-experimental nonequivalent group research design was used to evaluate students enrolled in an adult cardiac CAAHEP accredited echocardiography curriculum. Their cumulative final examination and clinical competency ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…While perceptions do not necessarily translate to outcomes, this finding may further support the difficulty and inaccuracy of clinical assessment. 1 An alternative option for future research could be to evaluate students' perceptions of clinical rotations affecting their ability to perform an echocardiogram competently.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While perceptions do not necessarily translate to outcomes, this finding may further support the difficulty and inaccuracy of clinical assessment. 1 An alternative option for future research could be to evaluate students' perceptions of clinical rotations affecting their ability to perform an echocardiogram competently.…”
Section: Discussionmentioning
confidence: 99%
“…The seven Likert questions administered only to the experimental group were fascinating relative to Dunstatter’s 1 findings. Dunstatter’s 1 study demonstrated no relationship between multiple competency-based assessments and students’ summative assessment grades and clinical competency evaluation scores given by clinical preceptors, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations